2017
DOI: 10.1111/vox.12622
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged platelet storage associated with increased frequency of transfusion‐related adverse events

Abstract: Prolonged storage of apheresis/irradiated PLTs was associated with a higher frequency of inflammation AEs. Apheresis/irradiated PLTs caused more AEs than WBD/nonirradiated PLTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
1
12
1
Order By: Relevance
“…Another recent study showed that prolonged storage of plasma platelets was associated with more inflammatory transfusion reactions (including FNHTRs, TRALI, transfusion‐associated dyspnea, and atypical reactions), but not with allergic reactions . Regarding allergic reactions, this other study is in agreement with our study.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Another recent study showed that prolonged storage of plasma platelets was associated with more inflammatory transfusion reactions (including FNHTRs, TRALI, transfusion‐associated dyspnea, and atypical reactions), but not with allergic reactions . Regarding allergic reactions, this other study is in agreement with our study.…”
Section: Discussionsupporting
confidence: 75%
“…Whether these changes also have clinical consequences is not clear yet, as published results are contradictory . A recently published review paper concludes that the risk of transfusion reactions was similar in old, compared to fresh, leukoreduced units, whereas a more recent study, not included in the review, showed that prolonged storage of platelets was associated with a higher frequency of inflammatory transfusion reactions but not allergic reactions …”
mentioning
confidence: 99%
“…6 PLTs of older storage age have been independently associated with adverse outcomes in certain adult cohorts including poorer response to PLT transfusions, 7 increased transfusion reactions, 8 and adverse inflammatory events. 9 Critically ill children are at particular risk of requiring PLT transfusions because of underlying organ dysfunction, including suppression of marrow and/or hepatic insufficiency, administration of medications that may suppress functional ability to clot, PLT consumption due to bleeding or microangiopathy, and frequent invasive procedures. PLT transfusions have been independently associated with increased mortality in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…PELOD-2 score of 7 (4)(5)(6)(7)(8)(9). However, they did not have significant worsening of their organ dysfunction 24 hours after the transfusion, as represented by a median (IQR) change in PELOD-2 score of 0 (−2 to 1).…”
Section: Unadjusted Clinical Outcomesmentioning
confidence: 92%
“…Multiple metabolic and signalling reactions that occur during the preparation and storage of platelet concentrates result in platelet activation and leads to accumulation of CD62P [78■■], sCD40L [79] and platelet microparticles (PMPs) [80■], and activation of coagulation factors and generation of mediators of inflammation and immunity, which interact with vascular endothelial cells and neutrophils [8183] (reviewed in [84■]). Transfusion of platelet concentrates containing activated platelets and mediators of inflammation and cellular injury has been linked to platelet transfusion-associated adverse events.…”
Section: Clinical Consequences Derived Of Storage Dependent Platelet mentioning
confidence: 99%